Investigating the morphology, locomotory performance and macroecology of a sub-Saharan African frog radiation (Anura: Pyxicephalidae) - Rebelo, Alexander Douglas (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.